Factors that predict complex reconstructions in facial skin cancer surgery. Issue 6 (14th July 2020) - Kravvas, Georgios; Walker‐Smith, Philippa; Skalsky, Helena; Keith, Daniel; Bray, Adam
Abstract: There is a paucity of high‐quality evidence and guidelines on the prediction of skin defect reconstruction, and the type of repair rests on the operating surgeon's experience and skill. Mismatches between planning and execution can have negative consequences on resources, staff, and patient counseling. To investigate the factors that predict complex reconstruction in facial skin cancer surgery, we performed a retrospective study collecting information on the several parameters that may affect the method of reconstruction. A total of 325 cases were included. Only the factors tumor size ( Z = 2.54; P  < .05) and predicted repair plan ( Z = 2.73; P  < .01) were found to be significant predictors of complex repairs. When broken down by site and size, only the nose, scalp, and temple demonstrated a significant correlation between tumor size and the need for complex repairs. Clinical judgment at the time of initial examination is by far the greatest predictor of complex repairs. This occurs even when clinicians have heterogeneous surgical skills, and most are not technically versed in complex repairs. Increasing tumor size was also found to be an independent risk factor albeit only at certain body sites such as the temple, scalp, and nose.